2021
DOI: 10.1371/journal.pone.0259545
|View full text |Cite
|
Sign up to set email alerts
|

Libidibia ferrea (jucá) anti-inflammatory action: A systematic review of in vivo and in vitro studies

Abstract: Libidibia ferrea (Mart. ex Tul.) L. P. Queiroz (jucá) is a plant extensively used in the Brazilian folk medicine for the treatment of the inflammatory process. Primary studies have focused on the verification of these biological activities, highlighting the role of this plant in inflammatory conditions. This systematic review aimed to critically establish which part of the plant and what type of plant extract present the highest evidence of anti-inflammatory activity as in vivo and in vitro experimental models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This protective effect could be attributed to antibacterial or antioxidant properties of the extract. Importantly, in mammals, L. ferrea is nontoxic ( Almeida et al, 2021b ), and we showed that EHMV is not toxic to CEs. Therefore, for the first time, in addition to its nontoxic effect, we demonstrated that EHMV can protect CEs in in vivo infection models.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This protective effect could be attributed to antibacterial or antioxidant properties of the extract. Importantly, in mammals, L. ferrea is nontoxic ( Almeida et al, 2021b ), and we showed that EHMV is not toxic to CEs. Therefore, for the first time, in addition to its nontoxic effect, we demonstrated that EHMV can protect CEs in in vivo infection models.…”
Section: Discussionmentioning
confidence: 57%
“…Among several species, Libidibia ferrea L.P. Queiroz ( L. ferrea ) is noteworthy and is popularly known as “Jucá” or “Pau-ferro” in Brazil. This species belongs to the Fabaceae family; is an endemic plant of the Brazilian flora and is distributed in the Caatinga; Atlantic Forest, and Cerrado biomes ( Almeida et al, 2021b ; Macedo et al, 2022 ). Several studies of L. ferrea have demonstrated the presence of bioactive compounds with antioxidant, antiulcerogenic, anti-inflammatory, analgesic, curative, and antibacterial activities, which are essential for treating various diseases ( de Araújo et al, 2014 ; Falcão et al, 2019 ; Macedo et al, 2022 ; Nascimento et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%